Respuesta :

Answer:

X= 3

Y= -2

Has to be negative to be able to equal zero.

Answer:

x = 3

y = -2

Step-by-step explanation:

4x + 5y = 2........i

2x + 3y = 0........ii

Let's start by eliminating x, so we multiply i by 2 and ii by 4

2|4x + 5y = 2

4|2x + 3y = 0

So that we have

8x + 10y = 4..........iii

8x + 12y = 0..........iv

Subtracting iv from III, we have

-2y = 4

y = 4/-2

y = -2

Going ahead and substituting this value of y in eqn i, we have

4x + 5(-2) = 2

4x - 10 = 2

4x = 2 + 10

4x = 12

x = 12/4

x = 3